2021
DOI: 10.1111/ajad.13215
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use disorder and increased risk of arrhythmia‐related hospitalization in young adults

Abstract: Background and Objectives: Recent observations indicate that cannabis use can result in cardiovascular complications including arrhythmias. We studied the relationship between cannabis use disorder (CUD) and arrhythmia hospitalization. Methods: We conducted a retrospective analysis of the Nationwide Inpatient Sample (2010-2014). Patients (age 15-54) with a primary diagnosis for arrhythmia (N = 570,556) were compared with non-arrhythmia (N = 67,662,082) inpatients for odds ratio (OR) of CUD by the logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
0
9
0
9
Order By: Relevance
“…Nevertheless, the origin of this association remained to be clarified. Cannabis is known to promote arrhythmias, including atrial fibrillation [14,24], vasospasm [13], autonomic dysregulation [25][26][27], and thrombogenesis [28], but the association with atheroma was not demonstrated so far. In our study, the association between cannabis use and atherosclerotic lesions was found using a multivariable model adjusting for potential confounders, including tobacco and illicit drugs other than cannabis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the origin of this association remained to be clarified. Cannabis is known to promote arrhythmias, including atrial fibrillation [14,24], vasospasm [13], autonomic dysregulation [25][26][27], and thrombogenesis [28], but the association with atheroma was not demonstrated so far. In our study, the association between cannabis use and atherosclerotic lesions was found using a multivariable model adjusting for potential confounders, including tobacco and illicit drugs other than cannabis.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies to date have explored the phenotype of stroke in cannabis users [13]. The hypotheses raised to explain the link between cannabis and stroke include an increased risk of cardiac arrythmia such as atrial fibrillation [14] and of reversible cerebral vasoconstriction syndrome (RCVS) [13]. The association of cannabis with atherosclerosis remains unclear, mainly because of coconsumption of tobacco and other illicit drugs [15].…”
mentioning
confidence: 99%
“…Similarly, Patel et al . found that CUD (diagnosed using ICD‐9 codes) was associated with higher odds of arrhythmia hospitalization among young adults, including in 15–24‐year‐olds [odds ratio (OR) = 1.28; 95% CI = 1.23–1.35] and 25–34‐year‐olds (OR = 1.52; 95% CI = 1.47–1.58) [55].…”
Section: Discussionmentioning
confidence: 99%
“…Bekannt ist auch, dass der akute Cannabiskonsum zu Herzrhythmusstörungen wie Vorhof- und Kammerflimmern 67 sowie in der Folge zu plötzlichem Herztod führen kann 21 , 68 . Stationäre Akutbehandlungen infolge von akuten Herzrhythmusstörungen sind bei jungen Erwachsenen mit einer Cannabinoidgebrauchsstörung signifikant deutlich häufiger als bei jungen Erwachsenen ohne eine Cannabinoidgebrauchsstörung 69 . Beachtet werden muss, dass synthetische Cannabinoide eine deutlich größere kardiovaskulären Toxizität als Produkte aus Cannabis (insbesondere Cannnabis sativa) aufweisen.…”
Section: Akute Somatische Störungsbilder Im Zusammenhang Mit Dem Gebr...unclassified
“…CHS spricht typischerweise nicht oder nur un zureichend auf konventionelle Antiemetika und Analgetika an, bessert sich aber deutlich beim warmen Duschen oder Baden[50,51]. Mögliche prokonvulsive Effekte (Senkung der "Krampfschwelle" mit höherem Risiko für epileptische rung[69]. Beachtet werden muss, dass synthetische Can nabinoide eine deutlich größere kardiovaskulären Toxizität als Produkte aus Cannabis (insbesondere Cannnabis sativa) aufweisen.…”
unclassified